2019
DOI: 10.1101/617373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Co-reviewing and ghostwriting by early career researchers in the peer review of manuscripts

Abstract: The goal of this study is to shed light on the involvement of early career researchers (ECRs) during peer review of manuscripts for publication in journals. In particular, we sought to better understand how commonly ECRs contribute ideas and/or text to peer review reports when they are not the invited reviewer ("coreview"), and how commonly ECRs do not receive named credit to the journal editorial staff for these scholarly efforts ("ghostwrite"). First, we evaluated 1,952 publications in the peerreviewed li… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…In addition, the efforts of ECRs, which are many and varied, are sometimes not acknowledged correctly or at all. For example, in one survey of ECRs in the life sciences, 92% of respondents reported that they had been involved in the peer review process, and more than half did so with no involvement of their supervisor 1,2 . To address these issues, Nature Reviews Endocrinology has committed to facilitating training in peer review and to ensuring that everyone involved in our peer review process is appropriately recognized (https://www.nature.…”
mentioning
confidence: 99%
“…In addition, the efforts of ECRs, which are many and varied, are sometimes not acknowledged correctly or at all. For example, in one survey of ECRs in the life sciences, 92% of respondents reported that they had been involved in the peer review process, and more than half did so with no involvement of their supervisor 1,2 . To address these issues, Nature Reviews Endocrinology has committed to facilitating training in peer review and to ensuring that everyone involved in our peer review process is appropriately recognized (https://www.nature.…”
mentioning
confidence: 99%
“…If you are interested in reviewing, you can ask a colleague who already reviews for a journal, or sits on an editorial board, to recommend you as a reviewer or help you learn the process through co-reviewing a manuscript. As a new initiative to facilitate co-review by early career researchers or clinicians and avoid ghostwriting, 1 our Editorial Board has established a process that allows for senior researchers or colleagues to formally mentor or delegate peer review duties to mentees when the opportunity arises. To initiate this process, an individual who has been invited to review for Prosthetics and Orthotics International can inform the Associate Editor that they would like to mentor another individual when they are invited to review a manuscript for the journal.…”
Section: Encouraging and Supporting New Reviewersmentioning
confidence: 99%
“…Earlier this year, a study blew away the cobwebs surrounding the issue of ghostwriting in the peer review process 4 . This global survey of almost 500 ECRs found that close to half of those questioned had received no credit for their contribution to reviewer reports and a further quarter did not know if their names appeared in the final version.…”
Section: P Rompted By Peer Review Week Atmentioning
confidence: 99%
“…We are also signed-up to Publons, where reviewers may record their work and find recognition for their contributions. Lack of recognition for their work may affect both the career progression and visa or residency eligibility of ECRs 4 . Although not all ECRs would benefit equally from receiving public credit for their work, Communications Physics believe all contributors should be provided with the choice to do so.…”
Section: P Rompted By Peer Review Week Atmentioning
confidence: 99%